Seeing patient longer at each consultation will improve their knowledge on diabetes but may not necessarily improve their diabetic control and metabolic parameters - Shahar , Mohammad Arif; Mohd Rafee, Adilah Rafi'ah; Mohamad Hazim, Husna; Saiful Bahri, Aina Sharleena; Mohamad, Rizman; Tuhiran, Mohd Fadzil (Malaysian Endocrine and Metabolic Society, 2014)
Objectives: To determine the association between consultation-time spent with doctors and patients’ knowledge, attitude and practice (KAP) on diabetic management, HbA1C and other metabolic parameters. Methods: This was a retrospective analysis of 291 type 2 diabetic patientswho attended our out-patient clinic. Their consultation time at previous two visits were reviewed and categorized into less or equal to 15 minutes, 15 to 30 minutes and more than 30 minutes. They were interviewed using a standardized KAP questionnaire on their diabetic management and most recent HbA1C and other metabolic parameters were recorded. Analysis was done using SPSS 19. Results: The mean age of respondent was56.5 ± 10.4 years old, where 57.7% were female. Median duration of diabetes was 6.0 (3.0,11.0) years. One third of patients completed primary level education and another third completed secondary level education. Sixty percent were unemployed or retired.Seventy-five percent of patients had 5-15 minutes spent seeing the doctor in the consultation room. Twenty percent had longer consultationtime (15 -30 min). Only 2% spent more than 30 minutes with the doctor during a consultation.Those who had longer consultation had higher knowledge and overall KAP score.However, there was no significant difference between both groups in terms of attitude and practice score. No significant difference were noted between longer and shorter consultations in terms of HbA1C, fasting blood sugar, weight, body mass index and cholesterol level. Conclusion: Those who had longer consultation time with doctors had better knowledge and overall KAP score. However, longer consultation time was not associated with better HbA1C and other metabolic parameters.